Analisis Taksonomi Bloom dalam Model Cooperative Learning Tipe Question Student Have - Akmal, Akmal (Pustaka Peradaban, 2024)
This study aimed to improve students' science learning outcomes through the implementation of the Cooperative Learning model, specifically the Question Student Have type, in fourth-grade students at SDN 230 Massenrengpulu, Sibulue District, Bone Regency. The research method employed was classroom action research (CAR), consisting of repeated cycles of planning, action implementation, observation, and reflection. The results showed that the application of the Question Student Have model significantly improved students' science learning outcomes. This improvement was accompanied by an increase in student involvement in the learning process, such as an increase in the number of questions asked and students' ability to answer questions. These findings are in line with Bloom's Taxonomy, which emphasizes the importance of appropriate instruction and formative assessment in achieving learning mastery for all students. This study suggests the need for further training for teachers in managing group discussions and implementing cooperative learning strategies, as well as the use of visual aids and technology to support more effective learning. Penelitian ini bertujuan untuk meningkatkan hasil belajar siswa dalam mata pelajaran IPA melalui penerapan model pembelajaran Cooperative Learning tipe Question Student Have pada siswa kelas IV SD Negeri 230 Massenrengpulu, Kecamatan Sibulue, Kabupaten Bone. Metode yang digunakan adalah penelitian tindakan kelas (PTK), yang terdiri dari siklus perencanaan, pelaksanaan tindakan, observasi, dan refleksi secara berulang. Hasil penelitian menunjukkan bahwa penerapan model pembelajaran Question Student Have secara signifikan meningkatkan hasil belajar IPA siswa. Peningkatan ini disertai dengan peningkatan keterlibatan siswa dalam proses pembelajaran, seperti peningkatan jumlah pertanyaan yang diajukan dan kemampuan siswa dalam menjawab pertanyaan. Temuan ini sejalan dengan teori Taksonomi Bloom, yang menekankan pentingnya instruksi yang tepat dan penilaian formatif dalam mencapai ketuntasan belajar bagi setiap siswa. Penelitian ini menyarankan perlunya pelatihan lanjutan bagi guru dalam pengelolaan diskusi kelompok dan penerapan strategi pembelajaran kooperatif, serta penggunaan alat bantu visual dan teknologi untuk mendukung pembelajaran yang lebih efektif.